Politics and religion. Cossacks’ alliances in the time of Bohdan Khmelnytsky - Franz, Maciej (Balcanica Posnaniensia. Acta et studia, 2011)
The article analyzes the relationship between politics and religion in the activities of the Cossacks during the uprising of Bohdan Khmelnytsky in the seventeenth century. The author examines the significance of Orthodoxy in Cossack ideology and the influence of religious issues on political and military alliances. The aim of the article is to assess the actual role of religion in Cossack politics and in the actions of Bohdan Khmelnytsky. The author employs an analysis of historical sources, Cossack universals, and literature concerning the history of Ukraine and the Cossacks. The study demonstrates that although the Cossacks often presented themselves as defenders of Orthodoxy, religious issues were in practice instrumental and subordinated to political and military goals. The author emphasizes that the alliance with the Crimean Khanate concluded in 1648 demonstrates that political considerations were more important than religious differences. The results of the analysis indicate that religion constituted an important element of Cossack propaganda, but did not unequivocally determine the political decisions taken by Cossack leaders.